Church and state in Italy in 2001 - Jouvenal, Danielle (European journal for church and state research, 2002)
Abstract der Zeitschrift: The Italian political situation is relevant to the description of State and Church relationships, as it is strongly affected by the physical presence of the Vatican in Rome and by the importance that most politicians attribute to the guidelines issued or indicated by the Vatican (and, for it, by the Italian Bishop's Conference) in the Italian political debate